Hospitalization Risk for Adults with Bipolar I Disorder Treated with Oral Atypical Antipsychotics as Adjunctive Therapy with Mood Stabilizers: A Retrospective Analysis of Medicaid Claims Data - Xiaoli Niu, PhD; Syvart Dennen, MPhil; Carole Dembek, MS; Kimberly Laubmeier, PhD; Yanmei Liu, MS; Phani Veeranki, MD, DrPH; Michael Tocco, PhD; G. Rhys Williams, ScD (Elsevier, 2021)
ABSTRACT: Background: Atypical antipsychotics (AAPs) with mood stabilizers are recommended as a first-line treatment for patients with bipolar disorder. No studies have compared the inpatient health care resource utilization for patients with bipolar disorder treated with lurasidone as adjunctive therapy with mood stabilizers compared with other oral AAPs.Objective: To compare the risk of hospitalization for adult Medicaid beneficiaries with bipolar I disorder when treated with lurasidone compared with other oral AAPs as adjunctive therapy with mood stabilizers.Methods: This retrospective cohort study used the MarketScan Research Databases Multi-State Medicaid Database (IBM, Armonk, NY) claims data to assess patients with bipolar I disorder between January 1, 2014, and June 30, 2019. Adult patients who initiated oral AAP treatment with mood stabilizers (index date) and who were continuously enrolled 12 months before (pre-index) and 24 months after (post-index) the index date were included. Treatment categories assigned by patient-month included lurasidone, aripiprazole, olanzapine, quetiapine, risperidone, or ziprasidone with mood stabilizers; no/minimal treatment; AAP monotherapy; and other. Marginal structural models were performed to estimate the all-cause and psychiatric hospitalization rates and hospital length of stay associated with each adjunctive AAP therapy by controlling for both time-invariant and time-varying confounders.Results: Adults with bipolar I disorder (N = 11,426; mean age = 39.4 years; female=73%) treated with an adjunctive oral AAP with mood stabilizers during the index month were categorized into lurasidone (12%), aripiprazole (17%), olanzapine (7%), quetiapine (32%), risperidone (11%), ziprasidone (7%), or other (15%) treatment groups. The adjusted odds of all-cause and psychiatric hospitalization were significantly higher for olanzapine (all causes: adjusted odds ratio [aOR] = 1.59; 95% CI, 1.13-2.25; psychiatric: aOR = 1.61, 95% CI, 1.12-2.32), quetiapine (all-causes: aOR = 1.27, 95% CI, 1.01-1.58; psychiatric: aOR = 1.28, 95% CI, 1.02-1.59), and ziprasidone (all-causes: aOR = 1.68, 95% CI, 1.05-2.66; psychiatric: aOR = 1.55, 95% CI, 1.02-2.35) compared with lurasidone with mood stabilizers. The adjusted odds of all-cause and psychiatric hospitalizations were numerically lower for lurasidone compared with aripiprazole. The all-cause hospital length of stay per 100 patient-months was significantly higher for olanzapine (20.3 days) and quetiapine (16.0 days) compared with lurasidone (12.2 days, both P values < 0.05).Conclusions: In a Medicaid population, adults with bipolar I disorder treated with lurasidone as adjunctive therapy with mood stabilizers had significantly lower all-cause and psychiatric hospitalization rates compared with olanzapine, quetiapine, and ziprasidone. Fewer hospitalizations may reduce the economic burden associated with bipolar disorder. (Curr Ther Res Clin Exp. 2021; 82:XXX-XXX)